2015
DOI: 10.1016/j.mod.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Roles of ADAM8 in elimination of injured muscle fibers prior to skeletal muscle regeneration

Abstract: Skeletal muscle regeneration requires processes different from developmental myogenesis. One important difference is a requirement of inflammatory reactions prior to regenerative myogenesis, by which injured muscle fibers must be eliminated to make new myotubes. In this study, we show that efficient elimination of injured muscle fibers during regeneration requires ADAM8, a member of a disintegrin and metalloprotease (ADAM) family. Skeletal muscle of dystrophin-null mice, an animal model for Duchenne Muscular D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…In agreement with our data, an increase in the expression of ADAM8 mRNA has been described in skin samples of SSc patients with leukocyte infiltration (Greenblatt et al, 2012). PSGL-1 is a target of ADAM8 (Domínguez-Luis et al, 2011;Gó mez-Gaviro et al, 2007;Nishimura et al, 2015); hence, the elevated levels of ADAM8 on SSc leukocytes could lead to a higher shedding of PSGL-1 when activated by other stimuli such as infections or tissue damage, decreasing the modulatory signals provided by PSGL-1 to the immune system. Supporting this notion, it was reported that a cohort of Japanese SSc patients presented higher concentrations of soluble PSGL-1 in serum (Yanaba et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our data, an increase in the expression of ADAM8 mRNA has been described in skin samples of SSc patients with leukocyte infiltration (Greenblatt et al, 2012). PSGL-1 is a target of ADAM8 (Domínguez-Luis et al, 2011;Gó mez-Gaviro et al, 2007;Nishimura et al, 2015); hence, the elevated levels of ADAM8 on SSc leukocytes could lead to a higher shedding of PSGL-1 when activated by other stimuli such as infections or tissue damage, decreasing the modulatory signals provided by PSGL-1 to the immune system. Supporting this notion, it was reported that a cohort of Japanese SSc patients presented higher concentrations of soluble PSGL-1 in serum (Yanaba et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…5F). Adam8 encodes a metalloprotease associated with skeletal muscle regeneration (38). Adam8 has not been previously linked to limb regeneration.…”
Section: Regeneration-specific Expression Pattern Of Select Genes Inmentioning
confidence: 99%
“…Invading neutrophils release proteolytic enzymes (e.g. ADAM-8 [40]) to degrade damaged muscle cells. The waning neutrophil influx is followed 24–48 h later by arrival of proinflammatory M1 macrophages and eosinophils recruited via cell-specific chemoattractants (e.g.…”
Section: Injury Inflammation and Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%